Velocity Vector Synthesis Method Based on Distributed Millimeter Wave Radar System - Ling, Minhao; Mao, Yinzhe; Zhao, Lou (Proceedings (International Conference on Communication Software and Networks), 2024)
In order to solve the problem of only obtaining the velocity vector size of the target when configuring a single radar and the possible mutual interference in multi radar systems, this paper proposes a velocity vector synthesis method, which utilizes the relationship between the velocity vector direction of the target and the angle of the radar relative to the target, combined with multi-source data fusion of multiple radars, to achieve the goal of target tracking and improve the estimation accuracy of specific target parameters. The results indicate that more accurate target localization results can be obtained, and the algorithm proposed in this paper has improved performance by about 70 % compared to traditional algorithms.